2020
DOI: 10.21037/acs-2020-surd-25
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of sutureless and rapid-deployment aortic valve replacement: a systematic review and meta-analysis

Abstract: Background: Sutureless and rapid-deployment aortic valve replacement (SURD-AVR) has become a prominent area of research as the medical community evaluate its place amongst other aortic valve interventions. The main advantages of SURD-AVR established to date are the reduced cross-clamp and cardiopulmonary bypass (CPB) times, as well as facilitating minimally invasive surgery in high-risk surgical patients. This current systematic review and meta-analysis, to our knowledge, is the first focusing on longterm outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
24
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
5
24
2
1
Order By: Relevance
“…SBs have demonstrated in large series and multicenter studies that they provide satisfactory results with low operative mortality, constantly improving outcomes, even when associated procedures are performed, and promising medium-term data [ 30 , 31 , 32 ]. Similar results have been reported with RDBs with regard to safety, hemodynamic performance, and favorable outcomes [ 33 , 34 , 35 , 36 ]. Based on the currently available data, both SBs and RDBs are considered valid alternatives to conventional prostheses for AVR.…”
Section: Discussionsupporting
confidence: 84%
“…SBs have demonstrated in large series and multicenter studies that they provide satisfactory results with low operative mortality, constantly improving outcomes, even when associated procedures are performed, and promising medium-term data [ 30 , 31 , 32 ]. Similar results have been reported with RDBs with regard to safety, hemodynamic performance, and favorable outcomes [ 33 , 34 , 35 , 36 ]. Based on the currently available data, both SBs and RDBs are considered valid alternatives to conventional prostheses for AVR.…”
Section: Discussionsupporting
confidence: 84%
“…Severe AS is also seen as a disease that is affected by nutritional status because it is common in the elderly, and long‐term outcomes of these patients are also the effect of malnutrition. Moreover, SAVR with sutureless/rapid‐deployment (SRD) prostheses could be useful especially in frailty 29 . However, Erfe et al 30 indicated that in SRD implantation, short‐term mortality, major comorbidities, and perivalvular regurgitation were similar between SRD and traditional stented bioprosthetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 The completeness of the presented data gives robustness to the very low 5-year incidence of major adverse cardiac and cerebrovascular events compared with previous analyses, with a particular focus on structural valve deterioration and reintervention. 5 But that's not all. This sponsored trial can also be considered a good reference point for benchmarking the surgical arm in the TAVI versus SAVR trials.…”
mentioning
confidence: 99%